Governance and New Mode of Governing: Indonesia as a Metaphor - Luqman nul Hakim (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2011)
Changes in global development policy orientation that put the community (society) rather than the state as its main target has been raised various debates about how to create a better society for development processes. This paper critically discuss the discourse of governance as an instrument of regulation in the new development model through some conceptual apparatus such as social capital, participation and deliberative democracy. Through a post-foundationalist approaches and studies of post-Suharto Indonesia, this paper examined the operation of governance discourse. The main thesis is that the absence of the dimension of power in governance has ignored the political configuration and even failed to notice the various interests in society.